Determining Undergraduate Students’ Environmental Att?tude - Yılmaz, Nihan; Erkal, Sibel (European Journal of Sustainable Development, 2017)
It has long been known that environmental issues and environmental issues are responsible for environmental problems. Young people’s environmental attitudes are particularly important because young people ultimately will be affected by and will need to provide solutions to environmental problems arising from present-day actions. This study aims to determine undergraduate students’ environmental attitudes.When the related literature is examined, it is seen that there are limited number of studies aiming to determine the attitudes of the university student towards the environment in general. For this reason, this study; has been planned and carried out in order to determine the environmental attitude of the students. 224 students studying at Hacettepe University have participated in this research made in order to determine the attitude of the students. In the study, a questionnaire composed of "Environmental Attitude Scale” has been used as a data collection tool. The average score of the environmental attitude levels of the students who participated in the study has been reported as ( =3,84). In conclusion, it was determined that undergraduate students’ environmental levels vary significantly by gender, family type status and level of income (p<0.01). Keywords: undergraduate students, environmental attitude, environmental behaviors, environmental thoght